Rapid progression of marginal zone B-cell lymphoma after COVID-19 vaccination (BNT162b2): A case report - Sekizawa, Akinori; Hashimoto, Kenichi; Kobayashi, Shinichi; Kozono, Sawako; Kobayashi, Takahiro; Kawamura, Yusuke; Kimata, Motohiro; Fujita, Naoya; Ono, Yosuke; Obuchi, Yasuhiro; Tanaka, Yuji (Frontiers in Medicine, 2022)
B-cell lymphomas are neoplastic diseases, sometimes associated with chronic inflammations. mRNA vaccines for coronavirus disease 2019 (COVID-19) induce inflammatory responses, which often develop fevers and lymphadenopathies indistinguishable from lymphomas. Although both could be influential, not many was known about their correlations. We herein report the first case of marginal zone B-cell lymphoma following mRNA COVID-19 vaccination. An 80-year-old Japanese woman presented with a right temporal lump that appeared the morning after she was administered her first mRNA COVID-19 vaccination (BNT162b2). The lump gradually decreased in size but persisted over 6 weeks after her first vaccination (3 weeks after her second vaccination). At her first visit to our hospital, ultrasound imaging revealed the size of the lump to be 28.5×5.7 mm, and computed tomography revealed multiple lymphadenopathies in the right parotid, submandibular, jugular, and supraclavicular regions. Initially, we suspected head-and-neck benign lymphadenopathy as a side effect of vaccination. Nine weeks later, the number of swollen submandibular and parotid glands had also increased and the maximum size of the pre-existing lymphadenopathies had enlarged. Finally, the right temporal mass was diagnosed as marginal zone B-cell lymphoma by immunohistochemical and flow cytometry findings of biopsy specimens. Although 4–6 weeks of observation for lymph node inflammation after the second vaccination is recommended, malignancy should also be considered in the differential diagnosis of lymphadenopathy following vaccination.